1990
DOI: 10.1073/pnas.87.22.8840
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human T-cell lymphotropic virus type 2 from Guaymi Indians in Panama.

Abstract: Human T-lymphotropic virus type I (HTLV-I) is associated with adult T-cell leukemia/lymphoma and with a chronic degenerative myelopathy. However, another major type of HTLV, HTLV-H, has been isolated only sporadically, and little is known of disease associations, transmission routes, and risk factors for HTLV-II infection. Recent studies indicate that a high percentage of-certain groups of i.v. drug users and blood donors are infected with HTLV-II.Seroepidemiologic studies have found an elevated rate of serore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(64 citation statements)
references
References 24 publications
0
63
0
1
Order By: Relevance
“…An HTLV-I-associated disease will develop in 3-8% of these infected individuals once in their lifetime (de The & Bomford, 1993;Gessain, 1996). HTLV-II has been shown to be endemic among various American Indian populations, including Navajos and Pueblos (New Mexico) (Hjelle et al, 1993) and Seminoles (Florida) (Biggar et al, 1996;Levine et al, 1993) in North America and the Guaymi in Panama (Lairmore et al, 1990;Pardi et al, 1993). In South America, a number of distinct populations in Colombia (Wayu, Guahibo, and Tunebo groups) Switzer et al, 1995), Argentina (Toba and Mataco) (Biglione et al, 1999), and Brazil (Kayapó and Krahô) (Black et al, 1994;Shindo et al, 2002) have been found to be infected with this virus.…”
Section: Human T-cell Lymphotropic Viruses Types I (Htlv-i) and Typementioning
confidence: 99%
“…An HTLV-I-associated disease will develop in 3-8% of these infected individuals once in their lifetime (de The & Bomford, 1993;Gessain, 1996). HTLV-II has been shown to be endemic among various American Indian populations, including Navajos and Pueblos (New Mexico) (Hjelle et al, 1993) and Seminoles (Florida) (Biggar et al, 1996;Levine et al, 1993) in North America and the Guaymi in Panama (Lairmore et al, 1990;Pardi et al, 1993). In South America, a number of distinct populations in Colombia (Wayu, Guahibo, and Tunebo groups) Switzer et al, 1995), Argentina (Toba and Mataco) (Biglione et al, 1999), and Brazil (Kayapó and Krahô) (Black et al, 1994;Shindo et al, 2002) have been found to be infected with this virus.…”
Section: Human T-cell Lymphotropic Viruses Types I (Htlv-i) and Typementioning
confidence: 99%
“…The very stable genome of these viruses provides an excellent tool for investigating the origin of PTLV in general and of HTLV-I and HTLV-II in particular (Gessain et al, 1992;Komurian et al, 1991 ;Liu et al, 1994a). The discovery of divergent Asian STLV-I (Song et al, 1994;Watanabe et al, 1986) and Asian and Australian HTLV-I strains (Bastian et aL, 1992;Gessain et al, 1993) together with the presence of HTLV-II among native Amerindians Lairmore et al, 1990;Maloney et al, 1992) support an Asian origin of PTLV. However, recent phylogenetic studies using divergent African and Asian STLV-I strains support an African origin of the African and cosmopolitan HTLV-I strains, and an Asian origin of the Melanesian and Australian HTLV-I strains, implying several separate interspecies transmissions (Koralnik et al, 1994;Saksena et al, 1994;Song et al, 1994;Vandamme et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HTLV-2 infection has been associated with sporadic cases of a myelopathy resembling HAM/TSP (Hjelle et al, 1992;Dooneief et al, 1996;Murphy et al, 1997), but has not been clearly linked with the development of lymphoproliferative disorders. HTLV-2 infection is highly concentrated in Central and West Africa (Gessain et al, 1993;Goubau et al, 1993), native Amerindian populations in North, Central, and South America (Hjelle et al, 1990;Lairmore et al, 1990;Heneine et al, 1991;Levine et al, 1993), and among cohorts of intravenous drug users (IVDUs) in the United States and Europe (Tedder et al, 1984;Robert-Guroff et al, 1986;Lee et al, 1989;Khabbaz et al, 1991;Toro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%